Hierarchical dispatch method for integrated heat and power systems considering the heat transfer process. (January 2021) - Jiang, Tuo; Min, Yong; Zhou, Guiping; Chen, Lei; Chen, Qun; Xu, Fei; Luo, Huanhuan
Abstract: The coordinated operation of integrated heat and power systems (IHPSs) is a promising solution for accommodating renewable energy and improving energy efficiency. A practical, effective dispatch method that coordinates the electric power system (EPS) and district heating system (DHS) is of great concern. This paper proposes a practical, non-iterative hierarchical dispatch method that introduces the concepts of the feasible region of boundary variables (FRBV) and optimal function of boundary variables (OFBV). In the proposed method, the private information of the DHS is protected in both the FRBV and OFBV. Moreover, they are transmitted between the EPS and the DHS operators only once to reduce communication overhead. This paper further proposes a method to conservatively estimate the FRBV and OFBV of the DHSs when the heat transfer process is considered in the model. Case studies are presented for an actual IHPS located in a northern city in China, and the results show that: 1) The heat generation capacity is over-estimated when the heat transfer process is not considered. 2) The hierarchical dispatch method obtains a larger regulating range of the combined heat and power units compared to those of the traditional "heat-led" operation mode and reduces the total coal consumption and the curtailed wind power by 4.46% and 38.50%, respectively. 3) The approximation-based hierarchical dispatch method obtains a solution that is less optimal than the exact method, but this difference in optimal value is less than 1%. Graphical abstract: Image 1 Highlights: A hierarchical dispatch method for integrated heat and power systems is proposed. Conservative approximations for calculating the operation range are proposed. The heat transfer process in the district heating system is taken into account. The properties of heat exchanger equations are discussed. Efficiency of the proposed approximation method is verified.